Distinguishing host responses, extensive viral dissemination and long-term viral RNA persistence in domestic sheep experimentally infected with Crimean-Congo haemorrhagic fever virus Kosovo Hoti - Hongzhao Li; Mathieu Pinette; Greg Smith; Melissa Goolia; Katherine Handel; Michelle Nebroski; Oliver Lung; Bradley S. Pickering (Emerging Microbes and Infections)
Crimean-Congo haemorrhagic fever orthonairovirus (CCHFV) is a tick-borne, risk group 4 pathogen that often causes a severe haemorrhagic disease in humans (CCHF) with high case fatality rates. The virus is believed to be maintained in a tick-vertebrate-tick ecological cycle involving numerous wild and domestic animal species; however the biology of CCHFV infection in these animals remains poorly understood. Here, we experimentally infect domestic sheep with CCHFV Kosovo Hoti, a clinical isolate representing high pathogenicity to humans and increasingly utilized in current research. In the absence of prominent clinical signs, the infection leads to an acute viremia and coinciding viral shedding, fever and markers for potential impairment in liver and kidney functions. A number of host responses distinguish the subclinical infection in sheep versus fatal infection in humans. These include an early reduction of neutrophil recruitment and its chemoattractant, IL-8, in the blood stream of infected sheep, whereas neutrophil infiltration and elevated IL-8 are features of fatal CCHFV infections reported in immunodeficient mice and humans. Several inflammatory cytokines that correlate with poor disease outcomes in humans and have potential to cause vascular dysfunction, a primary hallmark of severe CCHF, are down-regulated or restricted from increasing in sheep. Of particular interest, the detection of CCHFV RNA (including full-length genome) in a variety of sheep tissues long after the acute phase of infection indicates a widespread viral dissemination in the host and suggests a potentially long-term persisting impact of CCHFV infection. These findings reveal previously unrecognized aspects of CCHFV biology in animals.